Comparison of two self report questionnaires for depressive symptoms detection in pregnant women - Lam, Nelly (2009)
Objective: To determine the ability of two self-report questionnaires to detect depressive symptoms in the same pregnant women population. Design: Analytic, observational, cross sectional study. Setting: Instituto Nacional Materno Perinatal de Lima, Peru. Participants: Three hundred and seven pregnant women with no psychiatric history diagnosis attended during May-June 2008. Instruments: Edinburgh postnatal depression scale (EPDS) and Beck depression inventory (BDI-II). Results: Both scales had high average: 11,36 for EPDS (range: 0-26) and 15,96 for BDI-II (range 0-47). Internal consistencies were high (Cronbach’s alpha for EPDS was 0,826 and 0,815 for BDI-II). The Pearson correlation coefficient between both questionnaires was 0,541 (p<0,001). Conclusions: The study shows that both Edinburgh postnatal depression scale and beck depression inventory present high internal consistency and acceptable correlation. High averages found would show high probability in finding a depressive disorder in the mothers studied. Consequently we suggest a routine mental disorder screening at the Unidad de Medicina Fetal (Department of Fetal Medicine).